ANALISIS DAMPAK REBALANCING INDEX MSCI PADA PASAR MODAL SYARIAH INDONESIA SEBAGAI INSTRUMEN HALAL SHARIA-COMPLIANCE - Nur Syam Mario; Fachri Amir (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The development of the Islamic capital market in Indonesia has shown significant growth alongside the increasing interest of investors in Sharia-compliant investment instruments. One of the external factors that may influence the performance of Sharia stocks is the rebalancing of the Morgan Stanley Capital International (MSCI) Index, which is widely used by global institutional investors as a benchmark for portfolio allocation decisions. This study aims to analyze the impact of MSCI Index rebalancing on Indonesian Sharia stocks as halal and Sharia-compliant investment instruments. The research employs a descriptive qualitative approach using secondary data collected from various sources, including scientific journals, capital market reports, Indonesia Stock Exchange publications, MSCI reports, and other relevant literature on Islamic capital markets. The analysis is conducted through the examination and interpretation of findings related to changes in MSCI index composition and their implications for the performance of Sharia stocks in Indonesia. The results indicate that MSCI rebalancing affects liquidity, trading volume, and investor perception of Sharia stocks that are included in or excluded from the index. In addition to creating opportunities for increased foreign capital inflows, index adjustments may also generate short-term volatility in affected stocks. Nevertheless, the halal status of Sharia stocks remains determined by their compliance with Islamic principles rather than their inclusion in the MSCI Index. This study concludes that MSCI rebalancing has a strategic impact on the dynamics of the Indonesian Sharia stock market, particularly in enhancing its visibility and attractiveness to global investors.